Residual inflammatory risk and vulnerable plaque in the carotid artery in patients with ischemic stroke - Gong, Xiuqun; Yu, Chuanqing; Lu, Zeyu; Wang, Xia; Cai, Qiankun; Cheng, Xiaosi; Lu, Jun (Frontiers in Neurology, 2024)
Objective Inflammation is a central driver of atherogenesis and eventual plaque rupture. This study aimed to evaluate the association between residual inflammatory risk (RIR) and vulnerable plaques in the carotid artery in patients with ischemic stroke. Methods Patients with acute ischemic stroke were enrolled from January 2021 to July 2022. They were divided into four groups: RIR only (LDL-C <2.6 mmol/L and hsCRP ≥2 mg/L), residual cholesterol risk (RCR) only (LDL-C ≥2.6 mmol/L and hsCRP <2 mg/L), both risk or residual cholesterol and inflammatory risk (RCIR) (LDL-C ≥2.6 mmol/L and hsCRP ≥2 mg/L), and neither risk (LDL-C <2.6 mmol/L and hsCRP <2 mg/L). Vulnerable plaques were determined if it had a low attenuated plaque CT value of <35 Hounsfield Units (HU) and a remodeling index of >1.1, which indicated a positive remodeling. Results Out of the 468 enrolled patients, 157 (33.5%) were detected to have vulnerable plaques. The proportion of patients with neither risk, RIR, RCR, and RCIR were 32.9%, 28.6%, 18.8%, and 19.7%, respectively. Patients with vulnerable plaques exhibited a higher prevalence of hyperlipidemia (P = 0.026), higher proportion of RIR (P = 0.015), a higher ratio of stroke subtypes of large artery atherosclerosis (P = 0.012), and high leukocyte counts (P < 0.001). The logistic regression analysis detected that RIR was associated with vulnerable plaques after adjusted for major confounding factors (OR 1.98, 95% CI 1.13–3.45, P = 0.016), especially in the large artery atherosclerosis subtype (OR 2.71, 95% CI 1.08–6.77, P = 0.034). Conclusions In patients with ischemic stroke, RIR is associated with the vulnerability of carotid plaques, especially for those with the large artery atherosclerosis subtype. Therefore, further studies investigating the interventions to modulate inflammation in these patients may be warranted.